Photoelectrochemical performance of thermally sulfurized CdxZn1-xS photoanode: Enhancement with reduced graphene oxide support - ÖZKAYA, ALİ RIZA; KOCA, ATIF; SARIOĞLU, CEVAT; KARACA ALBAYRAK, FATMA; UĞUZ NELİ, ÖZLEM (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
In this study, photoelectrochemical performance of reduced graphene oxide (RGO)-CdxZn1-xS compos-ites, which were synthesized through a novel two-steps thermal sulfurization process by using elemental sulfur, was reported. This is the first time that the two-step thermal sulfurization process with elemental sulfur for the preparation of photoanode based on RGO-CdxZn1-xS. The electrodes exhibited high photostability and photocurrent response in the presence of visible light. The presence of RGO in CdxZn1-xS as electron collector and transporter increased the photocurrents approximately 40%. Among the RGOCdxZn1-xS composites, RGO-CdS photoanode yielded an extremely high photocurrent density of 6.5 mAcm(-2) with the rate of hydrogen production rate of 551.1mmolh(-1)cm(-2). This value of photocurrent density is almost 89% of its theoretical value. This is the maximum attained photocurrent density with superior stability in comparison with related literature. (c) 2020 Elsevier Ltd. All rights reserved.
Keywords: Photoelectrochemical water splitting; Spin coating; Sulfurization; Photocatalyst; Photoanodes; PHOTOCATALYTIC HYDROGEN-PRODUCTION; VISIBLE-LIGHT IRRADIATION; CD1-XZNXS SOLID-SOLUTIONS; H-2 EVOLUTION; CDS; EFFICIENT; SOLAR; ZNS; HETEROJUNCTION; COMPOSITES